Pendampingan Administrasi dan Proses Keberangkatan Mahasiswa Program Magang Internasional Taiwan - Dahniar Dahniar; Ahmad Hanafie; Mahadir Bin Amiruddin (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
International internships are an important means for students to gain cross-cultural work experience while improving their competitiveness in the global labor market. However, the administrative process for departing on an overseas internship is often a major obstacle for students, ranging from document processing, visa application, health examination, to funding. This community service activity aims to assist students of Universitas Islam Makassar through the administrative process until they were declared eligible and departed to join an international internship program in Taiwan. The assistance was carried out through several stages: socialization and initial selection, document and visa processing assistance, health examination facilitation, funding advocacy through collaboration with Lembaga Amil Zakat (LAZ) Kalla as sponsor, an official farewell ceremony led by the university rector, intensive mentoring through an online communication group during the internship period, and post-return evaluation. The results show that structured mentoring accelerated the completion of administrative requirements, reduced students' financial constraints through a sponsorship scheme, and maintained continuous communication and monitoring while students were in Taiwan. This activity is expected to serve as a model of international internship mentoring that can be replicated by other study programs or faculties within the university